Ferritic stainless steel
Patent Information
- Application Number
- JP2023128817
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
Smart Images

Figure 2025024598000003 
Figure 2025024598000001 
Figure 2025024598000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel material. [Background technology]
[0002] Ferritic stainless steel materials are inexpensive because they contain no Ni or only a small amount of Ni, but their applications are sometimes limited because they are inferior in corrosion resistance and workability to austenitic stainless steel materials.
[0003] In recent years, the expansion of applications of ferritic stainless steel materials has led to a demand for improved corrosion resistance of ferritic stainless steel materials. In particular, applications such as building panels and piping, which may be used in outdoor environments (e.g., outdoor corrosive environments such as salt damage environments), require the ability to suppress rusting and hole formation due to corrosion even in outdoor environments.
[0004] As a technique for improving the corrosion resistance of ferritic stainless steel materials, a method of adding alloy elements such as Cr and Mo is known (for example, Patent Document 1). However, in ferritic stainless steel materials, once corrosion (pitting corrosion) has occurred, it progresses faster than in austenitic stainless steel materials, so in order to slow down the rate of corrosion progression, it is necessary to add large amounts of Cr and Mo. However, adding large amounts of Cr and Mo would undermine the advantage of ferritic stainless steel materials, that is, their low cost.
[0005] In addition, a passive film (oxide film) containing amorphous oxides of Fe and Cr is formed on the surface of ferritic stainless steel, giving it corrosion resistance. -The barrier properties of ferritic stainless steel in a corrosive environment where halogen ions such as Cr, Cr, and Cr-containing ferritic stainless steel are present are not sufficient. The barrier properties in a corrosive environment where halogen ions are present are brought about by the amorphous oxide of Cr in the passive film, so a passivation treatment is known in which ferritic stainless steel is immersed in an acid such as nitric acid to concentrate Cr in the passive film. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 6-346195 Summary of the Invention [Problem to be solved by the invention]
[0007] However, even if passivation treatment using an acid is performed, the corrosion resistance of the ferritic stainless steel material is not sufficient, and since this passivation treatment uses an acid, it also has a large environmental impact.
[0008] The present invention has been made to solve the above problems, and has an object to provide a ferritic stainless steel material having excellent corrosion resistance. [Means for solving the problem]
[0009] The present inventors conducted extensive research into oxide films formed on the base material of ferritic stainless steel materials and discovered that an oxide film of a certain thickness in which Si is concentrated together with Cr is effective in improving corrosion resistance, leading to the completion of the present invention.
[0010] That is, the present invention provides a ferritic stainless steel material having a material part and an oxide film formed on the material part, The oxide film is a ferritic stainless steel material having a Si concentration of 3.0% or more, a Cr concentration of 20.0% or more, and a thickness of 10.0 nm or less. Effect of the Invention
[0011] According to the present invention, a ferritic stainless steel material having excellent corrosion resistance can be provided. [Brief description of the drawings]
[0012] [Figure 1] 1 is a graph showing the results of line analysis in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.
[0014] A ferritic stainless steel material (hereinafter sometimes abbreviated as "stainless steel material") according to an embodiment of the present invention has a material part and an oxide film formed on the material part. Here, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape. In addition, in this specification, "ferritic" means that the metal structure is mainly ferritic phase at room temperature. Therefore, "ferritic" also includes those that contain small amounts of phases other than ferritic phase (e.g., austenite phase, martensite phase, etc.). However, "ferritic" does not include a multi-phase structure of ferritic phase and austenite phase, a multi-phase structure of ferritic phase and martensite phase, or a multi-phase structure of ferritic phase, austenite phase, and martensite phase.
[0015] The oxide film is a passive film containing amorphous oxides with concentrated Cr and Si. The oxide film may further contain oxides of Fe and the like. The oxide film has a Si concentration of 3.0% or more and a Cr concentration of 20.0% or more. By making the oxide film contain Si and Cr at such concentrations, the barrier properties of the oxide film in a corrosive environment in which halogen ions are present are enhanced, thereby improving corrosion resistance. From the viewpoint of stably ensuring this effect, the Si concentration is preferably 3.2% or more, and more preferably 3.4% or more. From the same viewpoint, the Cr concentration is preferably 21.0% or more, and more preferably 23.0% or more. The upper limit of the Si concentration is not particularly limited, but is typically 20.0% or less, preferably 15.0% or less, and more preferably 10.0% or less. Similarly, the upper limit of the Cr concentration is not particularly limited, but is typically 50.0% or less, preferably 45.0% or less, and more preferably 40.0% or less.
[0016] The Si concentration and Cr concentration of the oxide film are obtained as follows. First, a sample is prepared by exposing a cross section of the stainless steel material in the thickness direction. Next, the sample is line-analyzed by TEM-EDX to obtain a component concentration profile in the depth direction, and the mass fractions of Cr, Si, and Fe are obtained at the position where the mass fraction of O (oxygen) is maximum. Using the obtained mass fractions of each element, the Si concentration can be calculated by the following formula (1), and the Cr concentration can be calculated by the following formula (2). Si concentration [mass%] = Si mass fraction [mass%] / (Cr mass fraction [mass%] + Si mass fraction [mass%] + Fe mass fraction [mass%]) × 100 (1) Cr concentration [mass%] = Cr mass fraction [mass%] / (Cr mass fraction [mass%] + Si mass fraction [mass%] + Fe mass fraction [mass%]) × 100 (2)
[0017] The oxide film is a film formed in a non-heated atmosphere (for example, at room temperature), and therefore has a small thickness. Specifically, the thickness of the oxide film is 10.0 nm or less, preferably 8.0 nm or less, and more preferably 6.0 nm or less. The lower limit of the thickness of the oxide film is not particularly limited, but from the viewpoint of stably ensuring the barrier properties of the oxide film, it is preferably 1.0 nm or more, more preferably 2.0 nm or more, and even more preferably 3.0 nm or more. The thickness of the oxide film is determined as follows. First, a sample is prepared by exposing the cross section of the stainless steel material in the thickness direction. Next, the sample is subjected to line analysis from the surface of the sample in the thickness (depth) direction using TEM-EDX, and the thickness of the oxide film is determined as the distance between the positions where the mass fraction of O (oxygen) is 1 / 4 of the maximum value in the obtained component concentration profile in the depth direction.
[0018] Here, a conventional oxide film formed by heat treating a ferritic stainless steel material in an air atmosphere has a structure in which an oxide layer mainly composed of Cr and Mn is present on the surface and SiO2 is present at the interface with the material. This oxide film does not satisfy the above-mentioned ranges of Si concentration and Cr concentration because Cr and Si are not both concentrated at the same position of the oxide film. In addition, this oxide film is thick because it is formed by heat treatment, and does not satisfy the above-mentioned thickness range. In addition, the conventional oxide film formed by heat treating ferritic stainless steel material containing Si in a low-oxygen atmosphere is a film mainly composed of SiO2 (a film with concentrated Si), but Cr is not concentrated and does not meet the above-mentioned Cr concentration range. Furthermore, this oxide film is thick because it is formed by heat treatment, and does not meet the above-mentioned thickness range.
[0019] The material part may have a composition including 1.00-3.00% Si and 13.00-32.00% Cr. The material part may further include 0.100% or less C, 1.00% or less Mn, 1.00% or less Ni, 0.100% or less P, 0.0020% or less S, 0.100% or less N, the total of Nb and Ti: 6(C+N)-0.700%, 2.00% or less Cu, 2.50% or less Mo, with the balance being Fe and impurities. If necessary, the material part may further contain one or more selected from Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
[0020] In this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and in the manufacturing process during industrial production of ferritic stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, impurities also include unavoidable impurities. With regard to the content of each element, "xx% or less" means that the content is xx% or less, but includes an amount exceeding 0% (particularly, exceeding the impurity level). Each component will be described in detail below.
[0021] (Si: 1.00~3.00%) Silicon is an element effective in improving the oxidation resistance, mechanical strength, corrosion resistance, and other properties of stainless steel materials. From the viewpoint of improving corrosion resistance (particularly, pitting resistance in a neutral environment such as salt water) among these properties, the lower limit of the silicon content is 1.00%, preferably 1.05%, and more preferably 1.10%. On the other hand, if the silicon content is too high, it acts as a solid solution strengthening element, leading to a decrease in workability and a decrease in weld toughness. Therefore, the upper limit of the silicon content is 3.00%, preferably 2.90%, and more preferably 2.80%.
[0022] (Cr:13.00~32.00%) Cr is an element effective in improving the corrosion resistance and oxidation resistance of stainless steel materials. In particular, from the viewpoint of ensuring corrosion resistance in consideration of outdoor salt damage environments, the lower limit of the Cr content is 13.00%, preferably 14.00%, and more preferably 15.00%. On the other hand, if the Cr content is too high, the manufacturing cost increases and it becomes difficult to ensure the toughness of the hot-rolled material, resulting in a decrease in manufacturability. Therefore, the upper limit of the Cr content is 32.00%, preferably 30.00%, and more preferably 25.00%.
[0023] (C: 0.100% or less) C is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. In particular, if the C content is too high, the workability and corrosion resistance of the stainless steel material will decrease. Therefore, the upper limit of the C content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the C content is not particularly limited, but excessively reducing the C content leads to an increase in refining costs. Therefore, the lower limit of the C content is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%.
[0024] (Mn:1.00% or less) Mn is an element effective for fixing S (desulfurization). However, if the Mn content is too high, MnS, which is the starting point of corrosion, is easily generated and the ferrite phase is destabilized. Therefore, the upper limit of the Mn content is 1.00%, preferably 0.80%, and more preferably 0.50%. On the other hand, the lower limit of the Mn content is not particularly limited, but from the viewpoint of obtaining the above-mentioned effect of Mn, it is preferably 0.01%, more preferably 0.02%, and even more preferably 0.05%.
[0025] (Ni: 1.00% or less) Ni is an element effective in improving the corrosion resistance of stainless steel materials, and has the effect of suppressing the progression of pitting corrosion and crevice corrosion in a low pH environment in particular. However, if the Ni content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Ni content is 1.00%, preferably 0.80%, and more preferably 0.60%. On the other hand, the lower limit of the Ni content is not particularly limited, but from the viewpoint of obtaining the above-mentioned effect, it is preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%.
[0026] (P:0.100% or less) P is an element that affects the properties of stainless steel materials, such as weldability and workability. However, if the P content is too high, the above properties may be deteriorated, so the upper limit of the P content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the P content is not particularly limited, but an excessively low P content leads to an increase in refining costs. Therefore, the lower limit of the P content is preferably 0.001%, more preferably 0.005%, and even more preferably 0.008%.
[0027] (S:0.0020% or less) S is an element that generates MnS, which is the starting point of corrosion, and affects the properties of stainless steel materials, such as corrosion resistance and weld toughness. In particular, if the S content is too high, the corrosion resistance decreases, so the upper limit of the S content is 0.0020%, preferably 0.0019%, and more preferably 0.0018%. On the other hand, the lower limit of the S content is not particularly limited, but excessively reducing the S content leads to an increase in refining costs. Therefore, the lower limit of the S content is preferably 0.0001%, and more preferably 0.0002%.
[0028] (N:0.100% or less) N is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. In particular, if the N content is too high, the weather resistance and workability of the stainless steel material are reduced. Therefore, the upper limit of the N content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the N content is not particularly limited, but excessively reducing the N content leads to an increase in refining costs. Therefore, the lower limit of the N content is preferably 0.001%, more preferably 0.003%, and even more preferably 0.005%.
[0029] (Total of Nb and Ti: 6(C+N)~0.700%) Nb and Ti are elements that affect the intergranular corrosion resistance (sensitization suppression effect) of stainless steel materials. In addition, since Nb and Ti are elements that are effective in fixing C and N, the total content of Nb and Ti is determined based on the amount of C and N. That is, the lower limit of the total content of Nb and Ti is 6(C+N)% from the viewpoint of obtaining the above-mentioned effect. However, if the total content of Nb and Ti is too high, in addition to increasing the manufacturing cost, the workability and surface quality of the stainless steel material are deteriorated. Therefore, the upper limit of the total content of Nb and Ti is 0.700%, preferably 0.600%, and more preferably 0.500%. In addition, the individual contents of Nb and Ti are each preferably 0.05% or more, more preferably 0.06% or more, from the viewpoint of suppressing the coarsening of crystal grains during annealing. In particular, Nb forms carbonitrides such as NbC and NbN, and the pinning effect of these carbonitrides can effectively suppress the coarsening of crystal grains.
[0030] (Cu:2.00% or less) Cu is an element effective in improving the workability and corrosion resistance of stainless steel materials. In particular, Cu has the effect of suppressing the progress of pitting corrosion in a low pH environment. However, if the Cu content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Cu content is set to 2.00%, preferably 1.50%, and more preferably 1.00%. On the other hand, the lower limit of the Cu content is not particularly limited, but is preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%, from the viewpoint of obtaining the effect of Cu.
[0031] (Mo: 2.50% or less) Mo is an element effective in improving the corrosion resistance and oxidation resistance of stainless steel materials. In particular, Mo has the effect of suppressing the progress of pitting corrosion in a low pH environment. However, if the Mo content is too high, it leads to a decrease in the workability of the stainless steel material and an increase in the manufacturing cost. Therefore, the upper limit of the Mo content is 2.50%, preferably 2.00%, and more preferably 1.50%. On the other hand, the lower limit of the Mo content is not particularly limited, but from the viewpoint of obtaining the effect of Mo, it is preferably 0.01%, more preferably 0.03%, and even more preferably 0.05%.
[0032] (Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less) Al, Zr, Co, V and W are elements effective for improving the oxidation resistance of stainless steel materials. However, if the content of Al, Zr, Co, V and W is too high, the workability and toughness of the stainless steel material will decrease, and the manufacturing cost will increase. Therefore, the upper limit of the content of Al, Zr, Co, V and W is 1.00%, preferably 0.95%, and more preferably 0.90%. On the other hand, the lower limit of the content of Al, Zr, Co, V and W is not particularly limited, but is preferably 0.001%, and more preferably 0.01%.
[0033] (REM: 0.100% or less, Ca: 0.100% or less) REM and Ca are elements effective for improving the oxidation resistance of stainless steel materials. However, if the REM and Ca contents are too high, it leads to an increase in manufacturing costs. Therefore, the upper limit of the REM and Ca contents is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the REM and Ca contents is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%. In addition, REM is a general term for Sc, Y, and lanthanoids, a total of 17 elements, and refers to rare earth metals. Specifically, La, Ce, Nd, etc. can be mentioned, and one of these can be contained alone or two or more can be combined. When two or more rare earth elements are contained, the content of the REM refers to the total content of these rare earth elements.
[0034] (Sn:0.100% or less) Sn is an element effective for improving the oxidation resistance of stainless steel materials. However, if the Sn content is too high, Sn segregates and the manufacturability of stainless steel materials decreases. Therefore, the upper limit of the Sn content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the Sn content is not particularly limited, but is preferably 0.001%, and more preferably 0.002%.
[0035] (B:0.0100% or less) B is an element effective for improving the secondary workability of stainless steel materials. However, if the B content is too high, the fatigue strength of the stainless steel material decreases. Therefore, the upper limit of the B content is 0.0100%, preferably 0.0090%, and more preferably 0.0080%. On the other hand, the lower limit of the B content is not particularly limited, but is preferably 0.0001%, and more preferably 0.0003%.
[0036] The ferritic stainless steel material according to the embodiment of the present invention has a pitting potential of 0.30 V vs. SSE or more. If the pitting potential is in this range, it is equivalent to the pitting potential of SUS4431J1, SUS304, etc., and therefore can be considered to have excellent pitting corrosion resistance. The pitting potential can be measured by the method described below.
[0037] The method for producing a ferritic stainless steel material according to the embodiment of the present invention is not particularly limited as long as it can produce a ferritic stainless steel material having the above-mentioned characteristics. Hereinafter, an example of the method for producing a ferritic stainless steel material according to the embodiment of the present invention will be described. The ferritic stainless steel material according to the embodiment of the present invention can be manufactured by wet polishing the surface of a stainless steel material having the above-mentioned composition to remove an oxide film, and then mirror finishing by wet polishing using colloidal silica. In particular, mirror finishing by wet polishing using colloidal silica can prevent the surface of the stainless steel material from being heated, so that a thin oxide film in which Cr and Si are concentrated can be formed. The conditions for wet polishing are not particularly limited, and may be appropriately adjusted according to a known method.
[0038] The stainless steel material used in the above manufacturing method is not particularly limited as long as it has the above composition, but is typically a rolled material. As the rolled material, a hot-rolled material, a cold-rolled material, etc. can be used. The rolled material can be manufactured according to a method known in the art. For example, the cold-rolled material can be manufactured by melting stainless steel having a predetermined composition, hot rolling, annealing, pickling, and then cold rolling. In addition, the rolled material may be subjected to various treatments (annealing, pickling, polishing, etc.) after rolling.
[0039] The ferritic stainless steel material according to the embodiment of the present invention produced as described above has excellent corrosion resistance and can be used in various applications where this property is required, such as building materials such as building panels, piping, etc. EXAMPLES
[0040] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.
[0041] Stainless steel having the composition shown in Table 1 (the balance being Fe and impurities) was melted and hot rolled to obtain a hot rolled sheet having a thickness of 3.0 mm, which was then annealed at 1050°C and pickled to obtain a hot rolled annealed sheet. Next, the hot rolled annealed sheet was cold rolled to obtain a cold rolled sheet having a thickness of 1.0 mm, which was then annealed at 1000°C in air for 1 minute and pickled to obtain a cold rolled annealed sheet. Next, a cold rolled annealed sheet sample having a size of 50 mm (rolling direction) x 50 mm (width direction) was cut out from the obtained cold rolled annealed sheet.
[0042] [Table 1]
[0043] (Examples 1 to 5 and Comparative Examples 1 to 2) Next, the cold-rolled annealed sheet sample was wet-polished using SiC abrasive paper with a grain size of #120 to remove the oxide film, and then further wet-polished using SiC abrasive paper with a grain size of #600. Thereafter, the sample was wet-polished using colloidal silica (average grain size 0.04 μm) as an abrasive to give it a mirror finish, thereby obtaining a stainless steel sheet sample.
[0044] Comparative Example 3 A stainless steel plate sample was obtained in the same manner as above, except that dry polishing using a grinder was carried out instead of wet polishing using colloidal silica.
[0045] The stainless steel sheet samples obtained above were subjected to the following evaluations.
[0046] (Si and Cr concentrations in oxide film) A test specimen was obtained in which the thickness direction cross section was exposed by processing the stainless steel plate sample at any position with a focused ion beam (FIB). Next, a line analysis was performed by TEM-EDX on the cross section (any three positions) of the test specimen. The line analysis was performed at a pitch of 0.1 mm from the surface of the test specimen in the depth direction. In the obtained component concentration profile in the depth direction, the mass fractions of the elements Cr, Si, and Fe were obtained at the position where the mass fraction of O (oxygen) was maximum. Using the obtained mass fractions of each element, the Si concentration and Cr concentration were calculated by the above formulas (1) and (2). The line analysis was performed using a scanning transmission electron microscope (STEM) HD-2700 manufactured by Hitachi High-Tech Corporation, which was equipped with an energy dispersive X-ray analyzer (DAX Octane T Ultra W) manufactured by Ametech Co., Ltd., and the acceleration voltage was set to 200 kV. As an example, the results of the line analysis (component concentration profile in the depth direction) in Example 1 are shown in Fig. 1. As shown in Fig. 1, in Example 1, the mass fraction of each element was determined at the position where the mass fraction of O was maximum (near a depth of 12.5 nm).
[0047] (Oxide film thickness) In the component concentration profile in the depth direction obtained in the same manner as above, the distance between positions where the mass fraction of O (oxygen) was ¼ of the maximum value was defined as the thickness of the oxide film. For example, in the line analysis results of Example 1 shown in FIG. 1, the thickness of the oxide film was determined as the distance between the positions where the mass fraction of O was ¼ (approximately 6.3 mass%) of the maximum value (approximately 25 mass%).
[0048] (Pitting potential) A stainless steel plate sample was sheared to prepare a test piece for measurement measuring 20 mm (rolling direction) x 15 mm (width direction). Next, a conductor was spot welded to one end of the test piece, and the test surface other than 10 mm x 10 mm was covered with silicone resin. A 3.5% aqueous NaCl solution was used as the test liquid, and Ar was degassed at 30°C. The test surface was completely immersed in the test liquid and left for 10 minutes, after which a potential sweep rate of 20 mV / min was used to measure the anode current density from the natural electrode potential to 500 μA / cm using a potentiostat.2 The potential was measured until the pitting potential reached 100 μA / cm on the anodic polarization curve. 2 The most noble potential among the potentials corresponding to the above was determined as the pitting potential (V). A saturated silver / silver chloride electrode (SSE) was used as the reference electrode. When the pitting potential is 0.30 V or higher, it can be determined that good pitting corrosion resistance equivalent to that of SUS443J1 and SUS304 has been obtained.
[0049] The above evaluation results are shown in Table 2.
[0050] [Table 2]
[0051] As shown in Table 2, the ferritic stainless steel sheets of Examples 1 to 5 had good corrosion resistance (pitting corrosion resistance) because the Si concentration, Cr concentration and thickness of the oxide film were within appropriate ranges. In contrast, the ferritic stainless steel sheet of Comparative Example 1 had insufficient corrosion resistance because the Si concentration in the oxide film was too low. The ferritic stainless steel sheet of Comparative Example 2 had insufficient corrosion resistance because the Cr concentration in the oxide film was too low. The ferritic stainless steel sheet of Comparative Example 3 was dry-polished, and thus the temperature rose during polishing, forming a thick oxide film. This oxide film had too low a Si concentration and Cr concentration, and was also thick, so its corrosion resistance was insufficient.
[0052] As can be seen from the above results, according to the present invention, a ferritic stainless steel material having excellent corrosion resistance can be provided.
Claims
1. A ferritic stainless steel material having a material portion and an oxide film formed on the material portion, The oxide film is a ferritic stainless steel material having a Si concentration of 3.0% or more, a Cr concentration of 20.0% or more, and a thickness of 10.0 nm or less.
2. The ferritic stainless steel material according to claim 1, wherein the material portion contains, on a mass basis, Si: 1.00 to 3.00%, Cr: 13.00 to 32.00%.
3. The ferritic stainless steel material according to claim 2, wherein the material portion further contains, on a mass basis, C: 0.100% or less, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, N: 0.100% or less, the sum of Nb and Ti: 6(C+N) to 0.700%, Cu: 2.00% or less, Mo: 2.50% or less, with the balance being Fe and impurities.
4. The ferritic stainless steel material according to claim 3, wherein the material portion further contains, by mass, one or more selected from Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
5. The ferritic stainless steel material according to any one of claims 1 to 4, having a pitting potential of 0.30 V vs. SSE or more.
Citation Information
Patent Citations
Highly corrosion-resistant ferritic stainless steel and its production
JP1994346195A